1982
DOI: 10.1111/j.1471-4159.1982.tb10866.x
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+‐Guanine Nucleotide Interactions in Brain Membranes. I. Modulation of Central 5‐Hydroxytryptamine Receptors in the Rat

Abstract: The present study indicates that central 5‐hydroxytryptamine (5‐HT; serotonin) receptors can be modulated in opposite directions by Ca2+ and guanine nucleotides [guanosine triphosphate (GTP), β, γ‐imidoguanosine 5′‐triphosphate (GppNHp)]. Thus CaCl2 (≥0.5 mm) inhibited whereas GTP and GppNHp (10 μm) stimulated the 5‐HT‐sensitive adenylate cyclase in the hippocampus of newborn rats. Both the affinity (Kd−1) and the number (Bmax) of [3H]5‐HT binding sites in hippocampal membranes from adult rats were increased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
29
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 31 publications
(34 reference statements)
7
29
0
Order By: Relevance
“…[3H]-5-HT binding Binding assays were performed essentially as described by Mallat & Hamon (1982) for membrane preparations of frontal cortex and hippocampus. In brief, tissue was homogenized in 30 volumes of 50mM Tris-HCl buffer, pH 7.4, with a Brinkman Polytron (setting 6-7, 15 s) and centrifuged for 20 min at 40,000 g. The resulting pellet was resuspended in an identical volume of buffer and recentrifuged.…”
Section: Neurochemical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…[3H]-5-HT binding Binding assays were performed essentially as described by Mallat & Hamon (1982) for membrane preparations of frontal cortex and hippocampus. In brief, tissue was homogenized in 30 volumes of 50mM Tris-HCl buffer, pH 7.4, with a Brinkman Polytron (setting 6-7, 15 s) and centrifuged for 20 min at 40,000 g. The resulting pellet was resuspended in an identical volume of buffer and recentrifuged.…”
Section: Neurochemical Proceduresmentioning
confidence: 99%
“…Nevertheless, conflicting reports have appeared regarding the potency of buspirone at 5-HT receptors in vitro (Riblet et al, 1982;Glaser & Traber, 1983) and the 5-HTergic qualities of buspirone in vivo (McMillen & Mattiace, 1983). Since blockade or disruption of 5-HTergic pathways has been implicated in the anticonflict actions of a number of compounds (Stein et al, 1977;Koe, 1979) (Hyttel, 1978) [3H]-5-HT binding Binding assays were performed essentially as described by Mallat & Hamon (1982) for membrane preparations of frontal cortex and hippocampus. In brief, tissue was homogenized in 30 volumes of 50mM Tris-HCl buffer, pH 7.4, with a Brinkman Polytron (setting 6-7, 15 s) and centrifuged for 20 min at 40,000 g. The resulting pellet was resuspended in an identical volume of buffer and recentrifuged.…”
Section: Introductionmentioning
confidence: 99%
“…tively mimics 5-HT in the activation of hippocampal adenylate cyclase, was not as potent as 5methoxytryptamine and bufotenin when tested for displacement of [3H]5-HT specifically bound to 5-HT recognition sites (Fillion et al, 1978). Two considerations may be adduced to explain this discrepancy: the [3H]5-HT binding assay requires ionic conditions which differ markedly from those used in the assay of the adenylate cyclase activity (Bennett and Snyder, 1976;Nelson et al, 1978;Mallat and Hamon, 1982); moreover, the 5-HT recognition sites coupled to the cyclic AMP generating system…”
Section: Hippocampal Location Of the Serotonin Receptors Coupled Withmentioning
confidence: 99%
“…Hence, it can be inferred that this multiplicity of synaptic responses derives from the coupling of apparently similar 5-HT, recognition sites to a variety of transducer mechanisms located in postsynaptic neural membranes. Previous reports have shown that GTP inhibits [3H]5-HT binding to brain membranes (Peroutka et al, 1979;Mallat and Hamon, 1982), indicating that the N (nucleotide regulatory component) (Rodbell, 1980) is operative in coupling 5-HT recognition sites with specific transducer mechanisms. Among others, an adenylate cyclase (ATP:pyrophosphate lyase (cyclizing), EC 4.6.1.1) may be one of the transducer mechanisms operative in certain 5-HT receptors, However, a 5-HT stimulation of adenylate cyclase could be found in crude synaptic membranes of hippocampi prepared from neonatal brain, but not in a similar preparation from adult brain (Von Hungen et al, 1975;., 1978a,6; Nelson et al, 1980a,b).…”
mentioning
confidence: 99%
“…The binding of GTP or /3, y-imidoguanosine 5'-triphosphate (GppNHp) (a potent analogue of GTP) to specific sites on such regulatory subunits both activates adenylate cyclase and decreases the affinity of numerous receptors for their respective agonists (Creese et al, 1979;Peroutka e t al., 1979;Tsai and Lefkowitz, 1979;Chang and Snyder, 1980; Childers and S n y d e r , 1980a; R o s e n b e r g e r e t al ., 1980;U'Prichard and Snyder, 1980;Wei and Sulakhe, 1980). In the case of the central serotonin (5-HT) receptor labelled with IJH]5-HT, G T P and G p p N H p also reduce the affinity of the specific binding site for the labelled neurotransmitter and other agonists (Peroutka et al, 1979;Hamon e t al., 1980;Mallat and Hamon, 1982). However, the inhibitory effects of guanine nucleotides on [3H]5-HT binding are variable because they depend on both the assay conditions and the characteristics of membranes.…”
mentioning
confidence: 99%